2001
DOI: 10.1002/app.10077
|View full text |Cite
|
Sign up to set email alerts
|

Study of cryostructuration of polymer systems. XXI. Cryotropic gel formation of the water–maltodextrin systems

Abstract: ABSTRACT:The freeze-thaw behavior of water solutions containing dissolved maltodextrin (MD; enzymatically converted potato starch derivative with MW of 8000 Da) over a wide range of MD concentration (0.1-15 g/dL) and freezing temperatures from Ϫ24 to Ϫ6°C was studied. Cryogenic treatment of these systems resulted in the formation of precipitates or gels, whose yield and thermal characteristics (fusion temperature and enthalpy) depended on the initial polymer concentration and conditions of freezing, frozen sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The proton frequently exchange between water and polysaccharide hydroxyl groups, which has a significant effect on the transverse relaxation mechanism of polysaccharide aqueous solution and gel. It is possible to calculate [29,30,31] the water proton transverse relaxation time with the help of a two-site exchange model. Investigations were made to study the hydration of chitosan and the water tightly coordinated with the polysaccharide in chitosan hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…The proton frequently exchange between water and polysaccharide hydroxyl groups, which has a significant effect on the transverse relaxation mechanism of polysaccharide aqueous solution and gel. It is possible to calculate [29,30,31] the water proton transverse relaxation time with the help of a two-site exchange model. Investigations were made to study the hydration of chitosan and the water tightly coordinated with the polysaccharide in chitosan hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Control experiments were performed where no TGase was added to the protein mixtures, in those cases no gels were formed after incubation up to 14 d. Thawing systems where TGase was not present simply resulted in reversing to the starting mixture. It has previously been shown that maltodextrin can form cryogels 35. In order to confirm that it was not the maltodextrin present in the TGase preparation that caused the gelation, casein and gelatin samples were prepared by heat treating the enzyme solution at 90 °C to denature TGase prior to mixing with the protein solution.…”
Section: Resultsmentioning
confidence: 99%
“…The cryogels formed from gelatinized starch [5,[70][71][72][73][74][75][76][77][78] (mentioned in Sect. 2.1) as well as those based on starch-polysaccharides [268,269] are also noncovalent cryogels that are stable at room temperature, but can be fused upon heating to C. There is also a special case of the formation of physical cryogels where the selfgelation processes occur at a high rate even at positive temperatures. The aqueous solutions of >1 wt% agarose or >5-10 wt% gelatine belong to this category of gel-forming systems.…”
Section: Physical (Noncovalent) Polymeric Cryogelsmentioning
confidence: 96%